1998
DOI: 10.1056/nejm199802193380803
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Compared with Individualized Chemotherapy for Childhood Acute Lymphoblastic Leukemia

Abstract: Adjusting the dose of methotrexate to account for the patient's ability to clear the drug can improve the outcome in children with B-lineage acute lymphoblastic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
264
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 438 publications
(267 citation statements)
references
References 20 publications
1
264
0
2
Order By: Relevance
“…5,29 Accordingly, some studies have shown that the cure rates or the degree of toxicity can be influenced by individualization of therapy based on the patients drug disposition or previous degree of toxicity. 41,42 One of the important challenges for hematologists is to improve the cure rates for adolescents and young adults to the level of that obtained for children. 43 To examine the biology of their leukemias, their pharmacology, treatment efficacy and pattern of side effects, as well as their compliance to therapy, adult hematologists in Denmark, Norway and Sweden will treat young adults between 18 and 45 years of age according to the NOPHO ALL-2008 protocol.…”
Section: Discussionmentioning
confidence: 99%
“…5,29 Accordingly, some studies have shown that the cure rates or the degree of toxicity can be influenced by individualization of therapy based on the patients drug disposition or previous degree of toxicity. 41,42 One of the important challenges for hematologists is to improve the cure rates for adolescents and young adults to the level of that obtained for children. 43 To examine the biology of their leukemias, their pharmacology, treatment efficacy and pattern of side effects, as well as their compliance to therapy, adult hematologists in Denmark, Norway and Sweden will treat young adults between 18 and 45 years of age according to the NOPHO ALL-2008 protocol.…”
Section: Discussionmentioning
confidence: 99%
“…British Journal of Cancer (2001) and reduce drug toxicity (Evans et al, 1998). However, with the exceptions of carboplatin, methotrexate and 6-mercaptopurine, no rational approach to individualized dosing of drugs administered to paediatric patients has emerged, and surface area is the most commonly used parameter with which to adjust doses for the wide range of body sizes encountered in paediatric oncology.…”
Section: Discussionmentioning
confidence: 99%
“…Drug clearance, and by definition systemic exposure, also shows wide inter-and intra-patient variation (Crom et al, 1987). This wide variation in systemic exposure may have a significant effect on disease response (Evans et al, 1998) and drug toxicity. Since changes in these physiological and pharmacokinetic parameters were thought to correlate most closely with Body Surface Area (BSA), it is this measurement which forms the basis of dose normalization with respect to variations in age, body size and body composition.…”
mentioning
confidence: 99%
“…etoposide [40,41]. TDM-guided dose individualization of methotrexate, teniposide and cytarabine has permitted the safe increase drug exposure in children with leukaemia [42], resulting in a signi®cant improvement in disease free as compared with conventional therapy.…”
Section: Discussionmentioning
confidence: 99%